Estimates of the cancer burden in Europe from radioactive fallout from the Chernobyl accident. - Cardis, E; Krewski, D; Boniol, M; Drozdovitch, V; Darby, S; Gilbert, E; Akiba, S; Benichou, J; Ferlay, J; Gandini, S; Hill, C; Howe, G; et al. (2006)
The Chernobyl accident, which occurred April 26, 1986, resulted in a large release of radionuclides, which were deposited over a very wide area, particularly in Europe. Although an increased risk of thyroid cancer in exposed children has been clearly demonstrated in the most contaminated regions, the impact of the accident on the risk of other cancers as well as elsewhere in Europe is less clear. The objective of the present study was to evaluate the human cancer burden in Europe as a whole from radioactive fallout from the accident. Average country- and region-specific whole-body and thyroid doses from Chernobyl were estimated using new dosimetric models and radiological data. Numbers of cancer cases and deaths possibly attributable to radiation from Chernobyl were estimated, applying state-of-the-art risk models derived from studies of other irradiated populations. Simultaneously, trends in cancer incidence and mortality were examined over time and by dose level. The risk projections suggest that by now Chernobyl may have caused about 1,000 cases of thyroid cancer and 4,000 cases of other cancers in Europe, representing about 0.01% of all incident cancers since the accident. Models predict that by 2065 about 16,000 (95% UI 3,400-72,000) cases of thyroid cancer and 25,000 (95% UI 11,000-59,000) cases of other cancers may be expected due to radiation from the accident, whereas several hundred million cancer cases are expected from other causes. Although these estimates are subject to considerable uncertainty, they provide an indication of the order of magnitude of the possible impact of the Chernobyl accident. It is unlikely that the cancer burden from the largest radiological accident to date could be detected by monitoring national cancer statistics. Indeed, results of analyses of time trends in cancer incidence and mortality in Europe do not, at present, indicate any increase in cancer rates -- other than of thyroid cancer in the most contaminated regions -- that can be clearly attributed to radiation from the Chernobyl accident.